Pathways to an integrated understanding of marine environments and ecosystems in the Asia-Pacific Region - Hanani Adiwira; Sayaka Yasunaka; Jamie M. Kass; Ayşe H. O. Açıkbaş; Sekar Adiningsih; Emma Gairin; Hovaldo B. C. Ilham; Elisa Lahcene; Yanguo Li; Gaku Nishihira; Paula Peñalver-Pereira; Florence M. P. Sie; et al. (Frontiers in Marine Science, 2025)
The Asia-Pacific Region (APR) encompasses a vast geographical area rich in marine biodiversity that plays critical roles in global ecological stability and climate regulation, but it also faces daunting challenges in maintaining these roles under global change. Environmental dynamics in the APR manifest regularly over a range of timescales, including storms, earthquakes, floods, and extreme heat events. Further, coastal and marine ecosystems, including extensive commercial fisheries and coral reefs, are under threat from intense resource extraction and increasingly frequent marine heatwaves. Knowledge gaps for understanding these complex systems are aggravated by substantial barriers to cross-national efforts caused by the region’s vast diversity of cultures, languages, socioeconomics, politics, and management practices. Effective management of marine resources in the APR will necessitate multidisciplinary research based on continuous, region-wide observations supported by robust collaborations. In 2023, we gathered APR researchers across disciplines to discuss these issues and find solutions during a thematic seminar and workshop program at Tohoku University in Japan. Based on the results of this program, we present a review of the current state of APR marine ecosystems, raise key questions addressable through multidisciplinary approaches, and identify future priorities for the region. We conclude that sustaining biodiversity, ecosystem functions, and climate resilience in the APR will depend on stronger interdisciplinary collaboration, better integration of biological and geophysical data, and broader access to marine observations. These efforts are both urgent and essential for supporting better science-based policy decisions to address the escalating effects of global change on marine systems across the region.

Status and prospects of biogeochemical Argo observations of chlorophyll-a in the northwest Pacific - Hakase Hayashida; Peter G. Strutton; Fuminori Hashihama; Naho Horimoto-Miyazaki; Toshiya Katano; Saori Yasui-Tamura (Journal of Oceanography, 2025)
Biogeochemical Argo (BGC-Argo) floats are autonomous marine observing platforms that monitor chlorophyll-a and other indicators of ocean ecosystem health globally. Since 2018, there has been an increase in the number of chlorophyll-a observations in the northwest Pacific due to the deployment of BGC-Argo floats. Such progress offers an unprecedented opportunity to develop a skillful operational ocean biogeochemical model. Here, we assess the performance of BGC-Argo floats in measuring chlorophyll-a concentrations and their spatiotemporal structures via comparison with satellite and shipboard data. Results show a good correlation ( r = 0.61) between the float and satellite observations and an excellent correlation ( r = 0.87) between the satellite and shipboard observations of sea surface concentrations. The float data have a bias of about 0.04 mg m −3 or 59 % with respect to the satellite observations. Rare matchups between the float and shipboard observations of winter and summer profiles in the upper 200 m reveal an excellent correlation ( r = 0.86), demonstrating the reliability of the vertical structure obtained from these floats. Concurrent two-year time series from five BGC-Argo floats reveal the prevalence of subsurface chlorophyll-a maxima in the subtropical northwest Pacific that can persist throughout the year. These findings stress the importance of subsurface monitoring to better quantify biological productivity and carbon export. We discuss the status of BGC-Argo floats in the northwest Pacific and recommend possible directions for modelling work and deployment efforts in achieving the proposed global array of 1000 floats in this decade, which has significant potential to improve predictability.

Subsurface chlorophyll maxima reduce the performance of non-photochemical quenching corrections in the Southern Ocean - Kimberlee Baldry; Peter G. Strutton; Nicole A. Hill; Philip W. Boyd (Frontiers in Marine Science, 2024)
Non-photochemical quenching (NPQ) within phytoplankton cells often causes the daytime suppression of chlorophyll fluorescence in the Southern Ocean. This is problematic and requires accurate correction when chlorophyll fluorescence is used as a proxy for chlorophyll-a concentration or phytoplankton abundance. In this study, we reveal that Southern Ocean subsurface chlorophyll maxima (SCMs) are the largest source of uncertainty when correcting for NPQ of chlorophyll fluorescence profiles. A detailed assessment of NPQ correction methods supports this claim by taking advantage of coincident chlorophyll fluorescence and chlorophyll concentration profiles. The best performing NPQ correction methods are conditional methods that consider the mixed layer depth (MLD), subsurface fluorescence maximum (SFM) and depth of 20% surface light. Compared to existing methods, the conditional methods proposed halve the bias in corrected chlorophyll fluorescence profiles and improve the success of replicating a SFM relative to chlorophyll concentration profiles. Of existing methods, the X12 and P18 methods, perform best overall, even when considering methods supplemented by beam attenuation or backscatter data. The widely-used S08 method, is more varied in its performance between profiles and its application introduced on average up to 2% more surface bias. Despite the significant improvement of the conditional method, it still underperformed in the presence of an SCM due to 1) changes in optical properties at the SCM and 2) large gradients of chlorophyll fluorescence across the pycnocline. Additionally, we highlight that conditional methods are best applied when uncertainty in chlorophyll fluorescence yields is within 50%. This highlights the need to better characterize the bio-optics of SCMs and chlorophyll fluorescence yields in the Southern Ocean, so that chlorophyll fluorescence data can be accurately converted to chlorophyll concentration in the absence of in situ water sampling.

Background nutrient concentration determines phytoplankton bloom response to marine heatwaves - Hakase Hayashida; Richard J. Matear; Peter G. Strutton (Global Change Biology, 2020)
Ocean temperature extreme events such as marine heatwaves are expected to intensify in coming decades due to anthropogenic global warming. Reported ecological and economic impacts of marine heatwaves include coral bleaching, local extinction of mangrove and kelp forests and elevated mortalities of invertebrates, fishes, seabirds and marine mammals. In contrast, little is known about the impacts of marine heatwaves on microbes that regulate biogeochemical processes in the ocean. Here we analyse the daily output of a near‐global ocean physical–biogeochemical model simulation to characterize the impacts of marine heatwaves on phytoplankton blooms in 23 tropical and temperate oceanographic regions from 1992 to 2014. The results reveal regionally coherent anomalies of shallower surface mixing layers and lower surface nitrate concentrations during marine heatwaves. These anomalies exert counteracting effects on phytoplankton growth through light and nutrient limitation. Consequently, the responses of phytoplankton blooms are mixed, but can be related to the background nutrient conditions of the study regions. The blooms are weaker during marine heatwaves in nutrient‐poor waters, whereas in nutrient‐rich waters, the heatwave blooms are stronger. The corresponding analyses of sea‐surface temperature, chlorophyll a and nitrate based on satellite observations and in situ climatology support this relationship between phytoplankton bloom anomalies and background nitrate concentration. Given that nutrient‐poor waters are projected to expand globally in the 21st century, this study suggests increased occurrence of weaker blooms during marine heatwaves in coming decades, with implications for higher trophic levels and biogeochemical cycling of key elements.

Subsurface Chlorophyll-a Maxima in the Southern Ocean - Kimberlee Baldry; Peter G. Strutton; Nicole A. Hill; Philip W. Boyd (Frontiers in Marine Science, 2020)

Identifying important species that amplify or mitigate the interactive effects of human impacts on marine food webs - Gary P. Griffith; Peter G. Strutton; Jayson M. Semmens; Elizabeth A. Fulton (Conservation Biology, 2019)
Some species may have a larger role than others in the transfer of complex effects of multiple human stressors, such as changes in biomass, through marine food webs. We devised a novel approach to identify such species. We constructed annual interaction‐effect networks (IENs) of the simulated changes in biomass between species of the southeastern Australian marine system. Each annual IEN was composed of the species linked by either an additive (sum of the individual stressor response), synergistic (lower biomass compared with additive effects), or antagonistic (greater biomass compared with additive effects) response to the interaction effect of ocean warming, ocean acidification, and fisheries. Structurally, over the simulation period, the number of species and links in the synergistic IENs increased and the network structure became more stable. The stability of the antagonistic IENs decreased and became more vulnerable to the loss of species. In contrast, there was no change in the structural attributes of species linked by an additive response. Using indices common in food‐web and network theory, we identified the species in each IEN for which a change in biomass from stressor effects would disproportionately affect the biomass of other species via direct and indirect local, intermediate, and global predator–prey feeding interactions. Knowing the species that transfer the most synergistic or antagonistic responses in a food‐web may inform conservation under increasing multiple‐stressor impacts.

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Climate change alters stability and species potential interactions in a large marine ecosystem - Gary P. Griffith; Peter G. Strutton; Jayson M. Semmens (Global Change Biology, 2018)
We have little empirical evidence of how large‐scale overlaps between large numbers of marine species may have altered in response to human impacts. Here, we synthesized all available distribution data (>1 million records) since 1992 for 61 species of the East Australian marine ecosystem, a global hot spot of ocean warming and continuing fisheries exploitation. Using a novel approach, we constructed networks of the annual changes in geographical overlaps between species. Using indices of changes in species overlap, we quantified changes in the ecosystem stability, species robustness, species sensitivity and structural keystone species. We then compared the species overlap indices with environmental and fisheries data to identify potential factors leading to the changes in distributional overlaps between species. We found that the structure of the ecosystem has changed with a decrease in asymmetrical geographical overlaps between species. This suggests that the ecosystem has become less stable and potentially more susceptible to environmental perturbations. Most species have shown a decrease in overlaps with other species. The greatest decrease in species overlap robustness and sensitivity to the loss of other species has occurred in the pelagic community. Some demersal species have become more robust and less sensitive. Pelagic structural keystone species, predominately the tunas and billfish, have been replaced by demersal fish species. The changes in species overlap were strongly correlated with regional oceanographic changes, in particular increasing ocean warming and the southward transport of warmer and saltier water with the East Australian Current, but less correlated with fisheries catch. Our study illustrates how large‐scale multispecies distribution changes can help identify structural changes in marine ecosystems associated with climate change.